Ekstraksi Sulit Benda Asing Kacang di Traktus Trakeobronkial: Sebuah Kasus Serial - Winata, Felicia Yumita; Sucipta, I Wayan; Dewantara, I Putu Santhi (PERHATI-KL, 2024)
Background: Tracheobronchial foreign body aspiration is a common emergency case, particularly in children. It happens mostly in children, causing airway obstruction and accidental death. Bronchoscopy is the gold standard of both diagnostics and therapeutics, but despite rapid developments in anesthesia techniques and bronchoscopic instrumentation, airway foreign body extraction is not an easy procedure to perform. Purpose: To demonstrate various approaches that can be employed to extract difficult tracheobronchial foreign bodies. Case report: This case report presented four cases of difficult extraction of peanut foreign body in the tracheobronchial tract that utilized different approaches of extraction. In all four cases, the foreign body was extracted successfully. Clinical question: What are the options available for difficult extraction of tracheobronchial peanut foreign body? Method: Evidence-based literatures study about approaches of tracheobronchial foreign body extraction was performed through PubMed, Google Scholar database, and hand searching/e-book. Result: A total of 5 relevant articles in pertaining to difficult extraction of tracheobronchial foreign bodies were found. Conclusion: There were multiple approaches for extracting tracheobronchial foreign body that could be costumized to each case. Keywords: tracheobronchial foreign body, peanut foreign body, difficult extraction ABSTRAK Latar belakang: Benda asing traktus trakeobronkial adalah salah satu kasus benda asing tersering pada keadaan gawat darurat. Kondisi tersebut paling sering terjadi pada anak-anak, menyebabkan sumbatan jalan nafas dan kematian. Bronkoskopi merupakan baku emas diagnostik sekaligus terapeutik, , akan tetapi walau telah terjadi perkembangan pesat dalam teknik anestesi dan instrumentasi bronkoskopi, ekstraksi benda asing di jalan napas bukan suatu prosedur yang mudah untuk dilakukan. Tujuan: Memaparkan berbagai pendekatan ekstraksi yang dapat dilakukan pada kasus sulit benda asing trakeobronkial. Laporan kasus: Dipaparkan empat kasus ekstraksi sulit benda asing kacang tanah di saluran trakeobronkial yang menggunakan pendekatan ekstraksi yang berbeda. Pada semua kasus, benda asing berhasil diekstraksi. Pertanyaan klinis: Apa saja pilihan pendekatan yang tersedia pada kasus ekstraksi sulit benda asing kacang trakeobronkial? Metode: Studi literatur berbasis bukti mengenai pendekatan ekstraksi benda asing trakeobronkial dilakukan melalui PubMed, basis data Google Scholar, dan pencarian manual/e-book. Hasil: Didapatkan 5 artikel yang relevan mengenai ekstraksi benda asing trakeobronkial. Kesimpulan: Terdapat beberapa pendekatan yang dapat digunakan untuk mengekstraksi benda asing trakeobronkial, yang dapat disesuaikan dengan masing-masing kasus. Kata kunci: benda asing trakeobronkial, benda asing kacang, ekstraksi sulit